DEMOGRAPHIC AND GENEALOGICAL STRUCTURE OF THE COSTEÑO CON CUERNOS COLOMBIAN CREOLE CATTLE - Cañas-Alvarez, Jhon; Garcés-Blanquiceth, Jorge; Paternina, Enoc; Quintero, David; Bejarano, Diego; Burgos-Paz, William; Ramirez Toro, Edison Julian (Chilean Journal of Agricultural & Animal Sciences, 2025)
The aim of this study was to assess the demographic structure and genetic diversity of the Costeño con Cuernos (CCC) Colombian creole cattle population using pedigree data. A total of 8,164 genealogical records of the CCC breed, spanning 1958 to 2023, were analyzed to estimate population censuses, effective population size, generational intervals, pedigree completeness, inbreeding coefficient, and effective number of founders. A progressive increase in population size was observed, reaching a population of 1,524 animals by 2022, with an average generational interval of 5.6 and 6.5 years for paternal and maternal lines, respectively. Pedigree completeness has significantly improved since the 1990s, reaching current values close to 100% over six generations. Inbreeding coefficients increased over time and estimates of effective population size were 253 and 89 based on census and inbreeding, respectively. Among the animals analyzed, 852 were found to have both parents unknown. The effective number of founders and ancestors was 69.6 and 42, respectively. The breed conservation strategy has maintained its genetic variability, but there is a need to incorporate new individuals into the Germplasm Bank.